The Impact of the EU Engagement in Serbia and Albania During the First Wave of COVID-19 - Bregu, Meljana (European Scientific Journal, ESJ, 2024)
Solidarity is a fundamental value of the European Union, alongside cooperation and competition. The COVID-19 pandemic tested the value of European solidarity; amid this unprecedented crisis, the EU initially failed to determine the most appropriate course of action. This provoked a strong reaction within the European Union and affected the EU’s position in the Western Balkans as a soft power. This paper examined the consequences for Serbia and Albania of the lack of solidarity that characterized the initial surge of the pandemic and the consequences on the integration process. The two countries were selected based on their dissimilar foreign policies. The paper aimed to explain the distinct effects of Russia’s and China’s foreign policy during the pandemic in Albania and Serbia. The core idea of the research was to evaluate the European intervention and aid during the first phase of the pandemic and the public opinion perception of the EU’s role in the two countries. The study collected the data of the Balkan Barometer surveys conducted in 2020 and 2021. Also, other data from the poll conducted by the International Republican Institute and various official statements and documents from the European Union were included in the study. As a brief conclusion, the study suggested that the EU’s role in the two countries during the first phase of the COVID-19 crisis was impacted by national factors like national politics and media narratives and also by the external influence of other actors like Russia and China.